Acute effects of vasoactive medications in patients with parallel circulation awaiting hybrid or Norwood procedure - Emily Hendon; Jennifer Kane; Gina M Golem; Amanda McBroom; Saul Flores; Joshua Wong; Enrique G Villarreal; Rohit S Loomba (Annals of Pediatric Cardiology, 2022)
Background : Vasoactive medications are frequently used in the preoperative stage to balance the pulmonary and systemic blood flow. However, not much is known about the effects of these agents during this stage. Aims : The primary objective of this study was to characterize the acute effects of vasoactive medications in children with parallel circulation before either the hybrid or Norwood procedure. Setting and Designs : This is a single-center, cross-sectional, retrospective study. Methods : Hemodynamic and systemic oxygen delivery data were captured from patients' vital signs, arterial blood gases, near-infrared spectroscopy monitoring (NIRS). Data for each patient were collected before the initiation of a vasoactive medication and again 6 h after. Statistical Analysis : Data were analyzed using paired t-tests, and analysis of covariance. Results : A total of 139 patients were identified. After data extraction the following patients were included before the initial intervention: 7 were on milrinone, 22 were on dopamine, and 17 were on dobutamine. Dopamine and dobutamine were found to significantly increase systolic blood pressure. Only dopamine increased pH (mean difference 0.04), decreased paCO2 (mean difference -7.1), decreased lactate (mean difference -0.6 mmol/L), and decreased in bedside Qp: Qs (mean difference -7.5) after continuous infusion for 6 h. Milrinone was not associated with any significant hemodynamic change. Conclusion : In this study, dopamine was independently associated with improvement in markers of systemic oxygen delivery 6 h after initiation. Dobutamine and dopamine were associated with increased in blood pressure. Well-powered studies are required to detect changes in lactate and NIRS.